Association between common laboratory indices and IgAV recurrence in children - Juan Zhou; Li Li; Jing Luo; Yingtian Yang; Xing Shen (BMC Pediatrics, 2022)
Abstract Background IgA vasculitis (IgAV) is a common type of vasculitis seen in children. IgAV recurrence can result in chronic kidney disease. We aimed to explore the association between common laboratory indices and IgAV recurrence in children, and to establish a prediction model. Methods This retrospective study included children with diagnosed with IgAV hospitalized in Bazhong Central Hospital, Sichuan, from January 2014 to December 2019. Children were assigned to two groups based on IgAV recurrence, and baseline clinical data were collected for comparison. A logistic regression model to predict IgAV recurrence was established. The receiver operating characteristic curve was plotted. The area under the curve (AUC) was used to detect performance of the predictive model. Results This study included 193 children (39 [20.2%], recurrence group; 154 [79.8%], non-recurrence group). Based on multivariate regression analysis, the duration of illness and joint involvement were independent predictors of IgAV recurrence in children (P < 0.05). No significant differences were observed in common laboratory indices (P > 0.05). The AUC of the prediction model was 0.766 (P < 0.001) with sensitivity of 74.4% and specificity of 68.8%. Conclusion Common laboratory indices were not associated with recurrence of IgAV in children.